2010
DOI: 10.1111/j.1365-2621.2010.02231.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition and flavonoids content of flour from different buckwheat cultivars

Abstract: Thirty nine buckwheat cultivars were collected from China, of which twenty one were tartary buckwheat and others were common buckwheat. Flour samples from these cultivars were analysed for colour properties, nutritional composition and flavonoid content. Buckwheat cultivars exhibited high variations for each of these parameters. The flour of common buckwheat showed a higher whiteness index than that of tartary buckwheat and contained very low levels of flavonoids. On average, the tartary buckwheat flour contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
6
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(130 citation statements)
references
References 17 publications
6
114
6
4
Order By: Relevance
“…Whiteness index showed a significant fall for the control sample, whilst the modified atmosphere packaging samples held the WI very well on day 14 (Rodriguez-Aguilera et al 2011). Qin et al (2010) analysed the nutritional composition and flavonoid contents of the flour from 39 buckwheat cultivars collected in China and compared the compositions of the flour from common buckwheat with those from tartary buckwheat. The flour of common buckwheat showed a higher whiteness index than that of tartary buckwheat and contained very low levels of flavonoids.…”
Section: Whiteness Indexmentioning
confidence: 99%
“…Whiteness index showed a significant fall for the control sample, whilst the modified atmosphere packaging samples held the WI very well on day 14 (Rodriguez-Aguilera et al 2011). Qin et al (2010) analysed the nutritional composition and flavonoid contents of the flour from 39 buckwheat cultivars collected in China and compared the compositions of the flour from common buckwheat with those from tartary buckwheat. The flour of common buckwheat showed a higher whiteness index than that of tartary buckwheat and contained very low levels of flavonoids.…”
Section: Whiteness Indexmentioning
confidence: 99%
“…The mean value of total flavonoids for the Fagopyrum esculentum cultivars was 0.372 mg rutin g -1 dw, what is 12.4 times less than in cultivar Lifago. Previous papers (Sedej et al, 2012;Kiprovski et al, 2015;Jambrec et al, 2015;Qin et al, 2010;Inglett et al, 2011) reported diverse content of total phenolics (0.6-5.4 mg GAE g -1 dw in Fagopyrum esculentum; 13.0 mg GAE g -1 dw in Fagopyrum tataricum), total flavonoids (0.07-3.8 mg rutin g -1 dw in Fagopyrum Tab. 1.…”
Section: Phenolics Analysismentioning
confidence: 99%
“…Cereal Research Communications 44, 2016 matory, and the improvement of plasma cholesterol, hypertension and diabetes (Couch et al 1946;Steadman et al 2001a;Milde et al 2004;Qin et al 2010;Choi et al 2015;Giménez-Bastida and Zieliński 2015). Therefore, buckwheat is recognized as an important raw material for functional food source in many countries, including China and Japan (Ötles and Cagindi, 2006;Bystrická et al 2011;Chen, 2012;Ahmed et al 2014).…”
Section: Liang Et Al: Characteristics Of High-yield Buckwheatmentioning
confidence: 99%